Impacts on Livestock Producers and Veterinarians of FDA Policies on Use of Medically Important Antibiotics in Food Animal Production. Issue 4 (18th May 2020) - Sneeringer, Stacy; Short, Gianna; MacLachlan, Matthew; Bowman, Maria
Abstract: U.S. Food and Drug Administration (FDA) policies fully implemented in 2017 ended the use of "medically important" (pertinent for human disease treatment) antibiotics for livestock growth promotion purposes. Between 2015 and 2017, medically important antibiotics sales for food animal production declined by 43%, after steady growth between 2009 and 2015. We examine the impacts of the antibiotics sales decline on livestock producers and veterinarians using case studies and empirical event studies. We find that the drop in sales did not impact overall meat production and that livestock producers engaged more heavily with their veterinarians to implement better management strategies.